Cooperative IRS and IOS-Aided Finite Blocklength Covert Communications in NOMA Networks - Li, Qiang; Xu, Dongyang; Liu, Lei; Du, Jianbo; Niyato, Dusit; Guizani, Mohsen (IEEE transactions on vehicular technology, 2025)
This paper proposes a finite blocklength covert non-orthogonal multiple access (NOMA) communication scheme based on cooperative intelligent reflecting surfaces (IRS) and intelligent omni-surfaces (IOS). To achieve covert transmission in the NOMA network, in the proposed scheme, the IRS switches between the IRS and IOS mechanisms to create uncertainty. To analyze the performance of this scheme, we first characterize the statistical properties of the users' cascaded channels. Then, we derive the closed-form expressions of the expectation of the Kullback-Leibler (KL) divergence and the average block error rates (BLERs) of NOMA users. To balance covertness and reliability, we formulate an optimization problem to maximize the effective covert throughput (ECT) subject to the reliability and delay constraints and the level of covertness. Via this optimization, we then obtain closed-form expressions for optimal power and blocklength. Simulation results demonstrate that the ECT of the proposed scheme is much higher than that of benchmarks.